Actuarial geometry - Stephen J. Mildenhall (Risks, 2017)
The literature on capital allocation is biased towards an asset modeling framework rather than an actuarial framework. The asset modeling framework leads to the proliferation of inappropriate assumptions about the effect of insurance line of business growth on aggregate loss distributions. This paper explains why an actuarial analog of the asset volume/return model should be based on a Lévy process. It discusses the impact of different loss models on marginal capital allocations. It shows that Lévy process-based models provide a better fit to the US statutory accounting data, and identifies how parameter risk scales with volume and increases with time. Finally, it shows the data suggest a surprising result regarding the form of insurance parameter risk.
Keywords: 330; capital; capital allocation; capital determination; diversification; homogeneous; insurance; insurance pricing; Lévy process; parameter risk; risk measure; risk theory